2021
DOI: 10.1016/j.eclinm.2021.101129
|View full text |Cite
|
Sign up to set email alerts
|

Transmission, viral kinetics and clinical characteristics of the emergent SARS-CoV-2 Delta VOC in Guangzhou, China

Abstract: Background A novel variant of SARS-CoV-2, the Delta variant of concern (VOC, also known as lineage B.1.617.2), is fast becoming the dominant strain globally. We reported the epidemiological, viral, and clinical characteristics of hospitalized patients infected with the Delta VOC during the local outbreak in Guangzhou, China. Methods We extracted the epidemiological and clinical information pertaining to the 159 cases infected with the Delta VOC across seven transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
204
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(229 citation statements)
references
References 23 publications
21
204
1
3
Order By: Relevance
“…Compared with the WT strain, the Delta strain harbored a significantly shorter median incubation period (4 days vs. 6 days), and was featured with a higher viral load (median Ct 20.6 vs. 34.0). Moreover, patients with Delta infection were associated with a shorter time of the deterioration to critical illness, a higher risk of critical status and longer period for RNA-negative conversion than WT (47). These clinical data confirmed that Delta carried unique properties that require continuous monitoring and follow-up.…”
Section: Major Genetic Variants Of Sars-cov-2supporting
confidence: 53%
“…Compared with the WT strain, the Delta strain harbored a significantly shorter median incubation period (4 days vs. 6 days), and was featured with a higher viral load (median Ct 20.6 vs. 34.0). Moreover, patients with Delta infection were associated with a shorter time of the deterioration to critical illness, a higher risk of critical status and longer period for RNA-negative conversion than WT (47). These clinical data confirmed that Delta carried unique properties that require continuous monitoring and follow-up.…”
Section: Major Genetic Variants Of Sars-cov-2supporting
confidence: 53%
“…SARS-CoV-2 strains with L452R and E484Q mutations were associated with heightened resistance to antibody neutralization ( 42 ). T478K mutation enhanced the infectivity and augmented the ability of SARS-CoV-2 to escape immune recognition ( 43 , 44 ). Each of the L452R and E484Q mutations lowered susceptibility to mRNA vaccine-generated antibodies by disrupting the binding between the RBD and hACE2, albeit the combined mutations did not show synergism ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Delta VOC is becoming the predominant lineage of SARS-CoV-2 in many countries (8,17). The presence of one of its most important mutation, L452R, does not necessarily mean the presence of a Delta VOC isolate, but, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%